CYBERSPACE LITERACY OF THE COLLEGE OF BUSINESS MANAGEMENT AND ACCOUNTANCY STUDENTS LAGUNA STATE POLYTECHNIC UNIVERSITY, STA. CRUZ, LAGUNA - Marilyn P. Pielago,Maryjan D.Fuentes (EPRA International Journal of Research and Development (IJRD), 2023)
Since 2015 studies reported that workplaces are dominated by millennials. However, tech savvy individuals occupy 75% of the workforce, they are lagging in the exercise of digital responsibility, passive towards environmental sustainability and fail to grasp the importance of social responsibility (Burgesss-Wilkerson et al, 2018; Fry, 2018). It was stated that in the next two decades, this new generation will be confronted with issues of global urgency amid demands for public action. The descriptive research method was considered to determine the Cyberspace Literacy of the College of Business Management and Accountancy Students Laguna State Polytechnic University, Sta. Cruz, Laguna. This method describes the characteristics of the population or phenomenon of the study. It primarily focuses on describing the nature of a demographic segment, without focusing on why the particular phenomenon occurs. (www.questionpro.com) The findings show a small positive correlation (r = 0.330) between the fathers’ educational attainment and cyberspace literacy as to digital communication. The result is direct showing that as the father’s educational attainment increases/high there is also an increase in terms of digital communication. On the other hand, the mothers’ educational attainment also shows a small correlation (r = 0.289) with cyberspace literacy as to digital skills. A positive correlation manifests a slanting upward direction which means that as one increases the other also increases that holds true both for father and mother educational qualifications. Other variables under consideration which are part of the study were all insignificant. Based on the findings of the study, the null hypothesis indicating that demographic profile, frequency and purpose of internet use has no significant relationship with cyberspace literacy is partially accepted/sustained.